If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + -1(2x + -2) = 6(x + -2) + 2 Reorder the terms: -24 + -1(-2 + 2x) = 6(x + -2) + 2 -24 + (-2 * -1 + 2x * -1) = 6(x + -2) + 2 -24 + (2 + -2x) = 6(x + -2) + 2 Combine like terms: -24 + 2 = -22 -22 + -2x = 6(x + -2) + 2 Reorder the terms: -22 + -2x = 6(-2 + x) + 2 -22 + -2x = (-2 * 6 + x * 6) + 2 -22 + -2x = (-12 + 6x) + 2 Reorder the terms: -22 + -2x = -12 + 2 + 6x Combine like terms: -12 + 2 = -10 -22 + -2x = -10 + 6x Solving -22 + -2x = -10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -22 + -2x + -6x = -10 + 6x + -6x Combine like terms: -2x + -6x = -8x -22 + -8x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 -22 + -8x = -10 + 0 -22 + -8x = -10 Add '22' to each side of the equation. -22 + 22 + -8x = -10 + 22 Combine like terms: -22 + 22 = 0 0 + -8x = -10 + 22 -8x = -10 + 22 Combine like terms: -10 + 22 = 12 -8x = 12 Divide each side by '-8'. x = -1.5 Simplifying x = -1.5
| -x^2-x+42= | | 6(y+2)-8=-2 | | 25p^2-5p-2= | | -4x^2-5y^2= | | 15x^2y^2+57xy^2-90y^2= | | 7x-3y= | | 2[b-(4b-5)]=3b+4 | | -20x+y=52 | | 16z+15z^2-15= | | 9k+10-7k+8= | | 6z+32=5z-9 | | 30m^2-11m-30= | | 9k+4b-7-5k+b= | | 21x^2-22xy+5y^2= | | 3z+8+2z+6= | | 35r^2+3r-2= | | 7x^2-34x-5= | | 9(7a-2)-2a= | | 10y^2-19y+9= | | 75x^2+40x-3=(5x+3) | | 5n=27 | | 2x^3-14x^2+20x= | | b=ym+y | | y^2(x-3)+8y(x-3)+15(x-3)= | | -16t^2+16t+192= | | 5n+6n^4-7n+15n^4+13n= | | 7x-26x^2=0 | | 20x-5-14x=22x-7-16x+11 | | -x^2+12x-11= | | 2(3+4x)-4=26 | | (R-3)(r+9)=89 | | 2x^6+14x^5+12x^4= |